Living on the edge: Forecasting the trends in abundance and distribution of the largest hoverfly genus (Diptera: Syrphidae) on the Balkan Peninsula under future climate change. (August 2017) - Radenković, S.; Schweiger, O.; Milić, D.; Harpke, A.; Vujić, A.
Abstract: Responses of hoverflies (Diptera: Syrphidae) to climate change remain mostly unexplored. Here, for the first time, we investigate the impact of climate change on both presence/absence and abundances of hoverfly species. We used generalized linear models to analyse the relationships of climatic and soil variables with the occurrence and abundance of Cheilosia species on the Balkan Peninsula. Our results show that the ranges of all and the abundances of many species are projected to decrease in the future. Climatically suitable conditions for mountainous species are predicted to generally shift northwards. Species adapted to high mountains are projected to almost vanish from the Balkans and only regions of the Alps would remain suitable for them. We found climatic variables were more important in determining abundance than occurrence. Given that environmental factors differed in terms of their impact on abundance and occurrence, we highlight the importance of monitoring both parameters to ensure effective conservation. Considering the different projected responses of hoverflies to future climate change, as well as their value as pollinators and the increasing threats they currently face, knowledge on their responses to the major drivers of their life-histories is indispensable for proper management and conservation action. We reveal that nationally-designated protected areas are insufficient to conserve the species considered here, both currently and under projected climate change. We recommend implementation of an integrated conservation management plan that can provide a continuum of protected areas along the Dinaric mountain chain to facilitate movement of species to enhance species survival. Highlights: We analyse impact of climate change on distribution and abundance of hoverfly genus. Ranges of all and abundances of many species are projected to decrease in the future. Climatic variables were more important in determining abundance than occurrence. High mountain species are projected to almost vanish from Balkan Peninsula by 2080. Nationally-designated protected areas are insufficient for species conservation.